2005
DOI: 10.1002/bem.20146
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ELF magnetic field tuned to Zn inhibits growth of cancer cells

Abstract: The effects of ELF alternating magnetic fields tuned to Zn(2+) on the growth of cancer cells with different status of p53 were investigated using a cell proliferation assay. Human cancer cells HeLa (cervix cancer, p53(+/+)), Saos-2 and Saos-2-His-273 (osteosarcoma, p53(-/-) and p53 His-273 mutant, respectively), H1299tTA and H1299tTA-His175 (lung carcinoma, p53(-/-) and p53 His-175 mutant), and normal human fibroblasts VH-10 (p53(+/+)) were used. Exposure parameters were calculated for the first harmonic of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
(34 reference statements)
3
20
0
Order By: Relevance
“…These MF conditions were selected since in our laboratory they have been associated with effects on [Ca 2þ ] c in vitro [McCreary et al, 2002] and on the response to a thermal stimulus in vivo [Prato et al, 1995[Prato et al, , 2000. In addition, the combination of timevarying and static MF satisfied the theoretical predictions of the ion resonance model and its variants [Lednev, 1991;Blanchard and Blackman, 1994], which have shown consistency with experimental results from other laboratories [Blackman et al, 1995;Baureus Koch et al, 2003;Sarimov et al, 2005].…”
Section: Introductionmentioning
confidence: 54%
“…These MF conditions were selected since in our laboratory they have been associated with effects on [Ca 2þ ] c in vitro [McCreary et al, 2002] and on the response to a thermal stimulus in vivo [Prato et al, 1995[Prato et al, , 2000. In addition, the combination of timevarying and static MF satisfied the theoretical predictions of the ion resonance model and its variants [Lednev, 1991;Blanchard and Blackman, 1994], which have shown consistency with experimental results from other laboratories [Blackman et al, 1995;Baureus Koch et al, 2003;Sarimov et al, 2005].…”
Section: Introductionmentioning
confidence: 54%
“…Among other ions, Zn 2+ is important and has been implicated in the biological effects of MFs. Presumably, this is associated with effects on Zn 2+ -containing proteins, including transcription factors and topoisomerases [30]. According to the results of Zn level measured in the present study, it can be suggested that long-term ELF-MF exposure (especially 500 μT) can alter Zn levels in the costa of rats.…”
Section: Discussionmentioning
confidence: 77%
“…In the final analysis what matters is whether the physiological response to magnetic fields follows the functional dependence of variables such as q/m, B AC , and/or o as these are expressed in one theoretical model or another. The various experimental reports [Blackman et al, 1995;Koch et al, 2003;Sarimov et al, 2005] that have explored this question unfortunately were not designed to test the present model. Nevertheless, it is clear that our model lends itself to straightforward experimental trials.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the explicit dependence on intensity allows one to design experiments to test Equation (1). A number of observers [Shuvalova et al, 1991;Blackman et al, 1994;Trillo et al, 1996;Prato et al, 2000;BerdenZrimec and Jerman, 2001;Koch et al, 2003;Sarimov et al, 2005] have reported results that are in part supportive of Equation (1) or the similar formulation by Blanchard and Blackman [1994]. Nevertheless, objections have arisen based on fundamental energy constraints [Adair, 1992] inasmuch as Equation (1) describes the probability for sub-thermal transitions between a pair of deeply energetic adjacent binding states.…”
Section: Introductionmentioning
confidence: 83%